Environmental Changes, Microbiota, and Allergic Diseases - Kim, Byoung-Ju; Lee, So-Yeon; Kim, Hyo-Bin; Lee, Eun; Hong, Soo-Jong (Allergy, asthma & immunology research, 2014)
During the last few decades, the prevalence of allergic disease has increased dramatically. The development of allergic diseases has been attributed to complex interactions between environmental factors and genetic factors. Of the many possible environmental factors, most research has focused on the most commonly encountered environmental factors, such as air pollution and environmental microbiota in combination with climate change. There is increasing evidence that such environmental factors play a critical role in the regulation of the immune response that is associated with allergic diseases, especially in genetically susceptible individuals. This review deals with not only these environmental factors and genetic factors but also their interactions in the development of allergic diseases. It will also emphasize the need for early interventions that can prevent the development of allergic diseases in susceptible populations and how these interventions can be identified.